2016
DOI: 10.4322/rca.2161
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos de solo degradado em função da adoção de biochar, culturas de cobertura e residual da aplicação de lodo de esgoto

Abstract: PALAVRAS-CHAVE Biofertilizante Área de empréstimo Resíduos agroindustriais KEYWORDS BiofertilizerBorrow area Agro-industrial waste RESUMO: O presente trabalho teve como objetivo avaliar as alterações nos atributos químicos do solo promovidas por adição do biochar, pela adoção de culturas de cobertura e pelo residual da aplicação de lodo de esgoto em área com solo em processo de recuperação após remoção da camada superficial. O delineamento adotado foi definido em blocos casualizados, em esquema fatorial 6 × 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Organically applied P, present in the biosolid composition, may show high resiliency due to the decomposition of the residue's organic matter and the consequent adsorption of the nutrient to the soil's mineral phase. Transition causes partial or total unavailability of P for plants (Vendruscolo et al, 2016). This has also been underlined by Martins et al (2015) in their study on the effect of the application of sewage sludge in soil conditioning.…”
Section: P and Kmentioning
confidence: 92%
See 1 more Smart Citation
“…Organically applied P, present in the biosolid composition, may show high resiliency due to the decomposition of the residue's organic matter and the consequent adsorption of the nutrient to the soil's mineral phase. Transition causes partial or total unavailability of P for plants (Vendruscolo et al, 2016). This has also been underlined by Martins et al (2015) in their study on the effect of the application of sewage sludge in soil conditioning.…”
Section: P and Kmentioning
confidence: 92%
“…On the other hand, Pires et al (2015) evidenced an increase in N rates after successive applications of sewage sludge. Vendruscolo et al (2016) found that the chemical characteristics of degraded soil might be positively affected, in the long run, by sewage sludge, with an increase in P and K availability. The above was also reported by Lourenzi et al (2016) when testing applications of organic compounds from shavings and liquid swine wastes which enhanced changes in pH and in P, K, Cu, and Zn rates of red latosol.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…O acúmulo de resíduos oriundos da atividade humana nos meios urbano e rural fez crescer a necessidade de estudar as formas mais adequadas de descartar resíduos urbanos e industriais, como o lodo de esgoto, o lixo urbano, resíduos de curtume e de aviários (ARAUJO et al, 2016;TAVARES FILHO;BARBOSA, 2016;VENDRUSCOLO et al, 2016). Em Mato Grosso o tipo de avicultura que mais se desenvolve é a de corte, seguida pela avicultura de postura e por fim da avicultura de reprodução.…”
Section: ____________________________________________________________unclassified
“…Os resíduos orgânicos são fontes de matéria orgânica para o solo, proporcionando a ele, maior qualidade estrutural (SCHIMIGUEL et al, 2014), além de terem a capacidade de fornecer nutrientes para as plantas e, consequentemente, reduz custos com a produção de mudas (ARAÚJO et al, 2017a). Outra vantagem para a agricultura é que, essa aplicação pode colaborar com a diminuição dos volumes de rejeitos que são, muitas vezes, armazenados de forma incorreta, acarretando em degradação ambiental, porque gera um produto que pode voltar ao campo na forma de fertilizante (VENDRUSCOLO et al, 2016).…”
Section: Introductionunclassified